SYNTHESIS OF FUNCTIONALIZED MCM-41 MESOPOROUS SILICA - Mermer, Nevin Karamahmut; Yilmaz, Muge Sari (CENTRAL BOHEMIA UNIV, 2017)
The invention of mesoporous materials is of significant interest to many scientists worldwide. The Mobil Crystalline Materials No 41 (MCM-41) is a well-known mesoporous molecular sieve that was discovered in 1992 by a scientist at the Mobil Oil Corporation. The MCM-41 is widely used in catalysis, ion exchange, drug delivery, optics, gas sensing, and sorption. In this study, the surface of a mesoporous silica MCM-41, synthesized from pure silica, is functionalized with a methyl group by grafting. The synthesized and functionalized samples are characterized by X-ray powder diffractometer (XRD), and the functionalized sample are also characterized by Fourier transform infrared spectroscopy (FTIR). The textural properties of the samples are determined using N-2 adsorption and desorption analysis. Thermal behaviors of the samples are analyzed using thermogravimetry (TG) and derivative thermogravimetry (DTG). The results of the analyses show that the functionalization of the synthesized material through grafting was accomplished with the surface area of the functionalized sample determined as 600.87 m(2) g(-1).
Keywords: MCM-41; grafting; methyl group; functionalization; XRD; CO2 ADSORPTION; AMINE; Business & Economics; Public Administration